Analysis of Marketing Strategy to Accelerate Business Growth of Painted Veil Dr. Kerudung Lukis - Mega Nuriza F Putri; Didip Diandra (Jurnal Ekonomi, 2018)
This research analyzes the marketing strategy which is implemented by DR. Kerudung Lukis. This research used case study methods to gather the data and observe the natural phenomenon which exists in a set of data. The objective of this final project is to assign the right marketing strategy for DR. Kerudung Lukis to accelerate their business growth. The result of analysis shows that DR. Kerudung Lukis need to improve their 7Ps marketing mix strategy in several aspects such as; First, DR. Kerudung Lukis should optimize it current products. Second, DR. Kerudung Lukis should optimize its current promotions strategies. Third, DR. Kerudung Lukis should hire more employees, and the last DR. Kerudung Lukis should add some physical evidences to increase their brand awareness